THE INFLUENCE OF INTELLECTUAL INTELLIGENCE AND EMOTIONAL INTELLIGENCE ON THE PERFORMANCE OF STUDENTS AT THE METRO STATE ISLAMIC RELIGIOUS INSTITUTE - Irpan Nurhab, Muhamad; Nurhab, Badaruddin; Aziz, Syaefudin (Jurnal Manajemen Bisnis Dan Organisasi, 2024)
To improve the quality of education at the Metro State Islamic Institute, the main focus should be directed toward improving human resource performance, particularly in terms of intellectual intelligence and emotional intelligence. The aim of this research is to examine the partial effect of intellectual intelligence on performance, the effect of emotional intelligence on performance, and the combined effect of intellectual intelligence and emotional intelligence on performance. The population of this study consisted of 43 students at the Metro State Islamic Institute. This research employed multiple linear regression analysis methods. Data were collected using a questionnaire. The results of hypothesis testing indicate that intellectual intelligence has a positive and significant effect on performance, emotional intelligence also has a positive and significant effect on performance, and both intellectual intelligence and emotional intelligence jointly have a positive and significant effect on performance.